Straight projection conflict detection and cooperative avoidance for autonomous unmanned aircraft systems - Albaker, B.M.; Rahim, N.A. (2009)
Flying multiple unmanned aircraft in the same airspace and instances or operating these aircraft in commercial airspace increases the likelihood of collisions. To facilitate the continuing growth of air traffic and the request for more operational flexibility a more advanced form of collision avoidance will be required. This paper, addresses the problem of solving conflicts raised between unmanned aircraft that are assumed to fly in same airspace and instances. In this framework, a new functional architecture for unmanned aircraft collision avoidance system is developed together with an algorithm utilized for deciding the collision criteria upon nominal state projection in the near future and sending the avoidance to the flight onboard computer based on heading and speed changes maneuvering. The collision avoidance system will allow each aircraft to negotiate with each another to determine a safe and acceptable solution when potential conflict is detected. The proposed approach uses cooperative, peer to peer negotiation technique in order to efficiently resolve air traffic conflicts.